Toward a Process Theory of Making Sustainability Strategies Legitimate in Action - Hengst, Iris-Ariane; Jarzabkowski, Paula; Hoegl, Martin; Muethel, Miriam (Academy of Management Journal, 2020)
We draw on a three-year qualitative study of the processual dynamics of implementing a sustainability strategy alongside an existing mainstream competitive strategy. We show that, despite the legitimacy of the sustainability strategy at the organizational level, actors experience tensions with its implementation at the action level vis-à-vis the mainstream strategy, thus creating the potential for decoupling. Our findings show that working through these tensions on specific tasks enables actors to legitimate the sustainability strategy in action and to co-enact it with the mainstream strategy within those tasks. Cumulatively, multiple instances of such co-enactment at the action level reinforce the organizational-level legitimacy of the sustainability strategy and its integration with the mainstream strategy. We draw these findings together into a dynamic process model that contributes to the literature on integration of dual strategies at the action and organizational levels as a process of legitimacy making.